2018
DOI: 10.1111/ijcs.12500
|View full text |Cite
|
Sign up to set email alerts
|

Influences of visual attributes of food packaging on consumer preference and associations with taste and healthiness

Abstract: Two experiments designed to investigate how the shape and colour of packaging, and product category, conjointly impact consumers’ product and packaging expectations are reported. In Experiment 1, the shape (rounded vs. angular) and visual appearance (greyscale, red‐to‐yellow and blue‐to‐green colour schemes) of the packaging were manipulated. Dependent measures were preference (willingness to purchase the product, how attention‐capturing the packaging is, and the pleasantness of the design) and any taste assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…Participants reported to frequently rely on package colour and images to categorise a product as healthy. Several studies have reported the relevance of visual attributes of food packaging in shaping healthiness perception (38,39) . Participants seemed to rely on other simple cues, such as nutrient claims, endorsement logos from scientific societies and brand, which have been previously reported to influence perceived healthiness (40)(41)(42) .…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported to frequently rely on package colour and images to categorise a product as healthy. Several studies have reported the relevance of visual attributes of food packaging in shaping healthiness perception (38,39) . Participants seemed to rely on other simple cues, such as nutrient claims, endorsement logos from scientific societies and brand, which have been previously reported to influence perceived healthiness (40)(41)(42) .…”
Section: Discussionmentioning
confidence: 99%
“…The second factor relates to the shape of the package; this study features two package shapes, namely bags and cylinders. This second factor was added to the design to avoid finding idiosyncratic effects suggesting that only glossy bags, for example, and no other glossy packages instigate fat level inferences (see Figure 2 for a picture of the packages that were used in this study), as prior research indicated that inferences derived from visual cues might differ according to package shape [20]. However, we had no a priori expectations on, nor explicit interest in, the effect of package shape on consumers' product inferences.…”
Section: Methodsmentioning
confidence: 99%
“…A diverse set of product beliefs, ranging from perceptions pertaining to product health and taste to product quality expectations, has been shown to be, at least in part, derived from product package design elements. For example, package shape (i.e., angular versus rounded packages, anthropomorphizing a package shape to mirror an ideal human body shape) and package color (i.e., less saturated versus more saturated colors) drive taste beliefs and even actual taste experiences [7,19,20]. Package colors can also influence the product's perceived healthiness, as research established highly saturated colors (versus lowly saturated colors) to improve health perceptions [21].…”
Section: Food Package Designmentioning
confidence: 99%
“…Package colour can be associated with a specific taste which can help rate a product when one cannot access it through experimentation [ 92 ]. The amount of orange colour on orange juice packaging increases sweetness expectations [ 91 , 93 ]. Food products in red packages were expected to be sweeter than those in green and blue packages [ 94 ] or white bowls [ 95 ].…”
Section: Object Processed Cuesmentioning
confidence: 99%
“…Food products in red packages were expected to be sweeter than those in green and blue packages [ 94 ] or white bowls [ 95 ]. Blue-to-green packaging was most strongly associated with a sour taste [ 93 ]. Green labels on beer bottles evoke higher taste ratings and indicate a dominance of fruity/citrus notes compared to a brown label [ 89 ].…”
Section: Object Processed Cuesmentioning
confidence: 99%